Effect of Feeding Rice Gluten Meal without or with Different Enzymes on Gut Health of Broiler Chickens - Dinani, Om Prakash; Tyagi, Pramod Kumar; Tyagi, Praveen Kumar; Mandal , Asit Baran; Jaiswal, Sudhir Kumar (International Journal of Livestock Research, 2019)
A biological experiment was conducted to evaluate the effect of feeding rice gluten meal (RGM) as soybean replacement without or with different enzymes on gut health in broiler chickens. The experiment was conducted as per 3x4 factorial completely randomized design. A total of 384 broiler chicks were divided into twelve different treatments with 4 replicates for each treatment and each replicate consisted of 8 chicks. Two levels of RGM were taken (15 and 17.5%). Mixing ratio 50 g per 100 kg feed for protease, 10 g per 100 kg feed for xylanase and 25 g per 100 kg feed for multienzymes were used as per manufacturer instructions. The study concluded that RGM feeding and their interaction with protease, xylanase and multienzymes revealed no significant (P>0.05) difference on intestinal histomorphometry and microbiological parameter of broiler chicken. However, xylanase enzyme supplementation improved gut health in rice gluten meal based diet in terms of improvement in villus height and reduction in total viable count in jejunum.